Analisa Persepsi Masyarakat Terhadap Dampak Lingkungan Usaha Sapi Perah di Kecamatan Pancoran - sholehah, siti; Ratnasari, Lisa (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The dairy cattle business in DKI Jakarta has been hereditary and has been increasing. This increase also has an impact on the environment around the farm, including pollution due to unpleasant odors, water pollution, soil pollution and the presence of annoying flies. The public's perception of the dairy business is very diverse, therefore the author conducted an analysis of the public's perception of the dairy business. Data collection was carried out in Pancoran District, South Jakarta, DKI Jakarta. Data was obtained through distributing questionnaires to residents and after interviews were processed using the ultrasound method and Linkert Scale. From the results of data processing, it was found that the community was disturbed by pollution due to unpleasant odors, water pollution, soil pollution and the presence of annoying flies. The proposal to overcome environmental impacts is made by turning cow faeces into organic fertilizer and biogas. Handling environmental impacts well can have a social impact and also provide many benefits to the surrounding community.